REGISTRATION OF COMPANIES IN INDIA - Rakshita Mathur (International Journal of Legal Developments & Allied Issues, 2023)
In this paper we shall explore the registration of companies in the Indian set-up. An insight will be seen into the steps which are followed to register the companies in this economy as well as the meanings of different companies.During the fiscal year 2021–2022, India received the greatest ever inflow of Foreign Direct Investment, totaling $83.57 billion.Under the Atmanirbhar Bharat Abhiyan (Self-reliant India) initiative, Hon. PM Shri Narendra Modi proposed a special economic and comprehensive package worth more than $270 billion, or 10% of India's GDP. According to projections, India's Gross Domestic Product ( also known commonly as the GDP of the country) would grow at the quickest rate in the world in 2022, 6.7%.The real GDP of India is anticipated to increase by 9% in 2021–22, 2022–23, and 7.1% in 2023–24. According to this forecast, India would have the world's fastest expanding major economy over the next three years.India is therefore a diverse and an exceptional economy that functions at a fast pace, especially in comparison to the rest of the world. This makes India an attractive option for investment.The focus shall lie of the process of the registration with regards to different domestic and foreign companies. Since the economy is continually changing, so too are investment and competitive methods. To maintain the economy's quick growth in light of India's economic structure, it is crucial to make procedures like registration appealing.